Correspondences between WZNW models and CFTs with W-algebra symmetry - Creutzig, Thomas; Hikida, Yasuaki; Rønne, Peter B. (Journal of High Energy Physics, 2016)
Abstract: We study theories with W-algebra symmetries and their relation to WZNW-type models on (super-)groups generalizing the H3+ WZNW to Liouville correspondence. Correlation functions of the WZNW models are expressed in terms of correlators of CFTs with W-algebra symmetry. The symmetries of the theories involved in these correspondences are related by the Drinfeld-Sokolov reduction of Lie algebras to W-algebras. The W-algebras considered in this paper are the Bershadsky-Polyakov algebra for sl(3) and the quasi-superconformal algebra for generic sl(N|M). The quantum W-algebras obtained from affine sl(N) are constructed using embeddings of sl(2) into sl(N), and these can in turn be characterized by partitions of N. The above cases correspond to N+ 2 = 2 + N1 and its supergroup extension. Finally, sl(2N) and the correspondence corresponding to 2N = N2 is also analyzed. These are all W-algebras that are generated by fields of at most dimension two.
CRIS-Team Scopus Importer:2024-06-24
Keywords: Conformal and W Symmetry; Conformal Field Models in String Theory